Collaborative teaching Introduction to Information Skills (IMC111) / Nurfaizah Kamarudin and Norlida Ismailly - Kamarudin, Nurfaizah; Ismailly, Norlida (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Collaborative teaching, or co-teaching, is an instructional approach where two or more educators work together to plan, deliver, and assess instruction in a shared classroom or learning environment. In this case, the lecturers of Introduction to Information Skills (IMC111) have taken the initiative to collaborate with Perpustakaan Tun Abdul Razak (PTAR), UiTM Sarawak, in imparting the designated topics to the students.